Monolithic Integration of Metalens in Silicon Photomultiplier for Improved Photodetection Efficiency. Issue 9 (15th March 2022) - Uenoyama, Soh; Ota, Ryosuke
Abstract: Silicon photomultipliers (SiPMs), consisting of 2D single‐photon avalanche diode (SPAD) arrays, have been widely used in many applications. In a SiPM, trench structures surround every SPAD to minimize optical crosstalk; however, these structures are photo‐insensitive areas. The previous study revealed that the use of metalenses for focusing incident photons on the photosensitive area of SPADs effectively improves the SiPM performance. However, ensuring good alignment between the metalens and SiPM has been difficult owing to its separated configuration. Herein the authors report the monolithic integration of a metalens with SPAD to provide stable photon detection efficiency (PDE) improvement, while maintaining the miniaturization and flatness of the optical device. The experiments demonstrate a maximum PDE improvement of ≈80% and robustness in incident‐angle‐dependent and wavelength‐dependent characteristics. In addition, a 2D PDE map across one SPAD cycle demonstrates that the metalens focuses incident photons impinging the trench area on the photosensitive area of the SPADs. Finally, scintillation emission is used to validate the improvement in timing resolution. These significant improvements will open new avenues for future advancements in SiPM performance. Moreover, the study shows the potential versatile application of metalenses at low cost based on complementary metal‐oxide semiconductor processes. Abstract : A sub‐pixel metalens, which is composed of HfO2 nanopillars, is directly formed on its corresponding single‐photon avalanche diode (SPAD) without alignment errors. The metalens focuses near‐ultraviolet incident photons on the center of the photo sensitive area of the SPAD, while avoiding impinging photo‐insensitive areas such as the trench area and some electrode patterning.